Avaliação do comportamento fluidodinâmico lı́quido-sólido em biorreatores de leito fluidizado utilizando técnicas de fluidodinâmica computacional (CFD) - Koerich, Daniela Maria (2018)
Anthropogenic actions have promoted technological challenges, for example, in the treatment of large quantities of wastewater, which can be done in fluidized bed bioreactors. For the study of these bioreactors, numerical techniques such as computational fluid dynamics (CFD) can be applied. However, in most of the literature available for multiphase systems, there are applications for gas-liquid or gas-solid systems. On the other hand, the dynamics in bioreactors is dominated by interactions between the liquid and solid phases. Thus, the aim of this study is to evaluate the hydrodynamic behavior of a liquid-solid fluidized bed bioreactor using CFD techniques. For the conduction of the simulations, a two-phase, Eulerian-Eulerian, transient and turbulent model was applied in a three-dimensional geometry, using the OpenFOAM code. Valid models have been established for the simulation of systems involving liquid-solid interactions, present in tapered fluidized bed bioreactors. Results showed the effect of the lift force on redistribution of bioparticles. Conversely, the coefficient of restitution did not affect significantly the height of the fluidized bed. The drag force estimate needed to be altered, and a dependency with the particles Reynolds number promoted good agreement of the fluidized bed height with experimental literature data. Using the validated model, it was observed that the study was conducted in the partially fluidized bed regime. None of the cases showed a meaningful presence of “dead zones”. Finally, it was noticed that both collisions between particles and shear stress (parameters that affect the biofilm thickness) occur concomitantly. Thus, greater bed expansion is not directly related to lower incidence of collisions between particles. The intensity of both parameters can be attenuated with the increased angle of the reactor.